A handbook of world trade : a strategic guide to trading internationally - Reuvid, Jonathan (Kogan Page ; ICC Pub., 2004)
This second edition of A Handbook of World Trade is a reliable reference source on the framework and mechanics of world trade. The guide examines the origins and nature of the WTO, regulatory issues and disputes in international trade, the management of foreign currencies in international trade, international trade finance and documentation, and international trade development issues.